Comprehensive Transcriptome Analysis Uncovers Hub Long Non-coding RNAs Regulating Potassium Use Efficiency in Nicotiana tabacum - Chen, Xi; Meng, Lin; He, Bing; Qi, Weicong; Jia, Letian; Xu, Na; Hu, Fengqin; Lv, Yuanda; Song, Wenjing (Frontiers in Plant Science, 2022)
Potassium (K) is the essential element for plant growth. It is one of the critical factors determining crop yield, quality, and especially leaf development in tobacco. However, the molecular mechanism of potassium use efficiency (KUE), especially noncoding RNA, is still unknown. In the study, tobacco seedlings were employed, and their hydro-cultivation with K treatments of low and sufficient concentrations were engaged. Physiological analysis showed that low potassium treatment could promote MDA accumulation and antioxidant enzyme activities such as POD, APX. After transcriptomic analysis, a total of 10,585 LncRNA transcripts were identified, and 242 of them were significantly differently expressed under potassium starvation. Furthermore, co-expression networks were constructed and generated 78 potential regulation modules in which coding gene and LncRNAs are involved and functional jointly. By further module-trait analysis and module membership ranking, nine modules, including 616 coding RNAs and 146 LncRNAs, showed a high correlation with K treatments, and 20 hub K-responsive LncRNAs were finally predicted. Following gene ontology analysis showed potassium starvation inducing the pathway of antioxidative-stress which is consistent with the physiology result mentioned above. Simultaneously, a part of detected LncRNAs such as MSTRG.6626.1, MSTRG.11330.1 and MSTRG.16041.1 were co-relating with a bench of MYB, C3H and NFYC transcript factors in response to the stress. Summarily, present research provided a set of LncRNAs responding to K concentration from starving and sufficient supplying. Simultaneously, the regulation network and potential co-functioning genes were listed as well. This massive dataset would serve as an outstanding clue for further study in tobacco and other plant species for nutrient physiology and molecular regulation mechanism.